Pulsatile nystagmus secondary to semicircular canal dehiscence. Issue 1 (22nd December 2018) - Hawwas, Mohamed; Young, Emily; Taneja, Virangna; Rejali, Darius
Abstract : We report the case of a 69-year-old man with a history of mastoidectomy for cholesteatoma, who developed spontaneous spinning vertigo on debridement of his cavity. Subsequent CT confirmed a lateral semicircular canal fistula, which was surgically closed with mastoid cavity obliteration. Following surgery, he developed a spontaneous, pulse-synchronous horizontal pendular nystagmus. We discuss the pathophysiology of this rare clinical sign.